(untitled) (Physical Education, Health and Social Sciences, 2024)
The recent, explosive assimilation of generative artificial intelligence (AI) technologies, like ChatGPT, Gemini, and Claude, into academic settings has led to the inextricable problematization of the fundamentals of authorship, academic integrity and the rules of ethical practice. Although these assistants are competent to perform relatively complicated linguistic tasks, such as the writing of a complete academic piece of work, the practice of their application has significantly exceeded the creation of the legal and institutional frameworks. The main question that the current paper aims to answer is whether the growing use of AI as a tool to create academic material is compatible with values and principles of academic integrity. Particularly, the paper will put into question the legality of AI-generated content and find analogies with the greater moral concept of legitimacy in the academy. Legally, there is no idea of AI as a writer in most jurisdictions. The regimes of copyright in the United States, United Kingdom, and European Union confirm that only human beings can be granting owners of original texts, and the written texts generated by AI, unless substantially changed by a human, are not subject to coverage by copyright protection. Nevertheless, AI usage without disclosure remains wide-spread among students and even those conducting studies, as it resides in a grey area of the law where action can be taken only in rare circumstance and where institutions have varied or no policies to guide them. Although this might not amount to a legal breach in the strict sense it brings with it considerable moral questions of intellectual integrity, disclosure and the genuineness of academic work. It is perhaps more urgent ethically than legally. Academic integrity has to do not just with plagiarism or with the technical rules, but with establishing habits of critical thought, original communication, and integrity with knowledge. When AI-written work is passed on anonymously, this compromises the educative purpose of academic writing and transform assessment into a performance project, instead of a learning project. In addition, the unacknowledged use of AI tools in the research setting damages the credibility of the record of scholarship, in particular when the tools create content that pays no regard to precision, context, or source integrity. The present paper holds that whether the use of AI in academia is legitimate or not, has nothing to do with whether or not the use of AI should be granted in academia; instead, what matters is whether the use of AI is in accordance with the letter and the spirit of academic values. The responsible eosinophilic framework of AI use should also comprise open declaration, a precise definition of the human effort of mind, and the responsibility of the end product. The issue of AI authorship and the active discussion going on concerning its possibility are also discussed in the paper, the conclusion is that the propositions on AI authorship should be declined because AI lacks consciousness, agency of morals, and responsibility to take towards the scholarly statements. To sum up, the given research states that not even legality can be seen as a factor defining whether AI-generated academic writing can be considered appropriate or not. Enhancing the academic integrity of research needs a wider cultural and institutional reinstatement similarly to the preservation of genuineness, justice, and pedagogical integrity of research in an era where scholars are being increasingly influenced by algorithmic ways.